2021
DOI: 10.3390/biology10101029
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machine-Based Classification of Vasovagal Syncope Using Head-Up Tilt Test

Abstract: Syncope is the medical condition of loss of consciousness triggered by the momentary cessation of blood flow to the brain. Machine learning techniques have been established to be very effective way to address such problems, where a class label is predicted for given input data. This work presents a Support Vector Machine (SVM) based classification of neuro-mediated syncope evaluated using train–test–split and K-fold cross-validation methods using the patient’s physiological data collected through the Head-up T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A model for vasovagal syncope classification using the Support Vector Machine (SVM)-based classification was presented in [ 16 ]. However, the work was limited to the use of the SVM in classification and lacked the exploration of other supervised machine learning models which could result in a better classification.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A model for vasovagal syncope classification using the Support Vector Machine (SVM)-based classification was presented in [ 16 ]. However, the work was limited to the use of the SVM in classification and lacked the exploration of other supervised machine learning models which could result in a better classification.…”
Section: Discussionmentioning
confidence: 99%
“…The test for this study found three main underlying mechanisms responsible for the triggering of the induction of syncope, viz. a sudden drop in blood pressure, drop in heart rate resulting in a drop in blood pressure and a continual drop in blood pressure as reported in [ 16 ].…”
Section: Syncope Classification Modelmentioning
confidence: 94%
See 3 more Smart Citations